Youth Subcultures as a form of Protest to Authoritarian Regime (on the Example of Soviet Ukraine in the 1950s-1980s) - Soroka, Svitlana (Studia Warmińskie, 2019)
The reasons for the emergence of a youth subculture in Ukraine in the 1950s are analyzed in the article. The main types of subcultures, their ideology and features of activity are studied. The author shows the evolution of the youth subculture depending on socio-political changes in the country and analyzes the main ways of authority fighting against youth subcultures. The role of youth subculture in an authoritarian society on the example of Soviet Ukraine in the 1950-1980 years is defined.